NILAI-NILAI RELIGIUS DALAM SYAIR SHALAWAT BURDAH - Setiawan, Eko (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2015)
Shalawat Burdah is poetic expression of love Imam Bushiri to Prophet Muhammad SAW. Moral values contained in the blessings Burdah among others about taubat, zuhud, patience, sincerity, tawakal, mahabbah. Shalawat Burdah meets the characteristics of the propagation of Islam: first, the art of worship and blessings clearly contain beads, because it contains the teachings of Islam about the blessings of the Prophet Muhammad Saw and the lyrics are loaded with rosary to God. Second, the real blessings containing shades of coolness and a reflection of the religious attitude of a person or a group. The art of giving identity blessings upon the lives of the Muslims can be seen and felt by others.